Educational Management Information System Governance in Islamic Secondary Schools - Rif’an Humaidi; Sarwan (Journal of Educational Management Research, 2026)
The rapid advancement of information and communication technology has made Management Information Systems (MIS) an essential component in modern educational institutions. This study aims to examine the management of infrastructure and human resources in supporting the operation of Educational Management Information Systems. A qualitative descriptive approach was employed. Data were collected through observations, in-depth interviews, and documentation to obtain a comprehensive understanding of MIS management practices. The findings reveal that infrastructure management is carried out through continuous improvement of hardware and software capacity, as well as the enhancement of internet network reliability. Meanwhile, human resource management focuses on improving staff competencies through information technology training and capacity-building programs. These efforts contribute to more effective, efficient, and responsive administrative services within educational organizations. The study implies that successful implementation of Educational Management Information Systems requires integrated management of technological infrastructure and human resources. Educational institutions are encouraged to prioritize digital readiness and continuous professional development to ensure the sustainability and effectiveness of MIS-based services in the digital era.